The effect of hypokalemia in pregnancy on fetal heart rate - Febriani; Nofiandi, Riki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Hypokalemic myopathy can cause anything from weakness and numbness to total paralysis. The cause could be acquired or congenital. It is distinguished by low potassium levels (<3.5 meq/L) and severe muscle weakness. We present a case of 30-year-old multigravida at 31 weeks of gestation with malnourished condition, who came with acute onset of weakness of both legs. She was diagnosed to have hypokalemic paralysis with potassium levels of 1.5 meq/L. The medical profile remitted promptly on intravenous potassium replacement. Pregnancy was continued till 37 weeks with oral potassium supplements and regular monitoring of serum potassium levels.